On the use on hydroxyapatite suspensions for the separation of milk fat globule membrane components from buttermilk. (15th March 2023) - Iung, J.; Pouliot, Y.; Remondetto, G.; Jiménez-Flores, R.; Brisson, G.
Abstract: The milk fat globule membrane (MFGM), which surrounds and stabilizes the fat globules, is released in buttermilk during cream churning. MFGM has many health benefits due to its composition rich in phospholipids and membrane proteins. Many techniques have been tried to separate the MFGM from the remaining milk solids non-fat, but they are challenging to carry out at an industrial scale. This research proposes a new approach to separating MFGM from buttermilk. This paper assessed the efficacy of hydroxyapatite (HA) cristal in interacting with MFGM isolates obtained from either raw or pasteurized cream. Different HA to MFGM ratios were used (10:1 and 20:1) to determine the impact of HA concentration on the adsorption. The results showed a very high affinity of the MFGM for HA and suggested the potential for its separation from buttermilk to improve its valorization.